Estimation of the economic burden of atrial fibrillation-related stroke in Greece. (3rd April 2022) - Vemmos, Konstantinos; Boubouchairopoulou, Nadia; Stafylas, Panagiotis; Vitsou, Elli; Giannakoulas, George; Ntaios, George; Milionis, Haralampos; Hahalis, George; Parthenakis, Frangiskos; Tsioufis, Konstantinos
ABSTRACT: Background: Stroke is aleading cause of death and disability, with atrial fibrillation (AF) being among key risk factors and AF-related stroke inflicting significant burden on healthcare systems and society. The present study was undertaken for estimating the total annual socioeconomic burden of AF-related stroke in Greece and identifying the key cost contributors. Research design and methods: A cost-of-illness model was developed for estimating the total annual economic burden of AF-related stroke in Greece, from asocietal perspective (year 2018). Atargeted literature review and an advisory board consisting of key experts in the management of AF and AF-related stroke were performed for collecting local resource use and epidemiological data. Results: The total annual socioeconomic burden of AF-related stroke was estimated at €175million, in 2018. Direct and indirect costs accounted for 59% and 41%, respectively. Main contributors were informal care (21.1%), patients' productivity losses (19.7%) and hospitalizations (15.0%), accounting for more than half of the total costs of AF-related stroke events. Conclusion: A F-related stroke imposes asignificant socioeconomic burden in Greece. Despite results relying on estimations, it seems that ensuring efficient reallocation of resources in appropriate prevention and early intervention strategies could decrease AF-related stroke's burden but also enhance healthcare systems' efficiency. Abbreviations: AF=atrial fibrillation